2015
DOI: 10.1007/s10584-014-1314-x
|View full text |Cite
|
Sign up to set email alerts
|

An uncertainty approach to assessment of climate change impacts on the Zambezi River Basin

Abstract: Many residents of the Zambezi River Valley are dependent on water-related resources. Greenhouse gas (GHG) emissions may cause a significant change to the climate in the Zambezi Basin in the future, but there is much uncertainty about the future climate state. This situation leaves policy makers at a state of urgency to prepare for these changes as well as reduce the impacts of the changes through GHG mitigation strategies. First and foremost, we must better understand the economic sectors most likely impacted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
4
12
0
Order By: Relevance
“…Irrigation demands are likely to be unmet in Mozambique and Zimbabwe, and hydropower generation is likely to be reduced in Zambia. 36,44 According to the simulations, air temperature and potential evaporation are projected to increase, while rainfall is projected to decrease, which together contribute to a decrease in river flows. Consequently, the decrease in water resources will lead to decreased hydropower production potential, by 9% in 2020s, 18% in 2050s and 28% in 2080s in the hydropower system, using A1B emission scenario.…”
Section: Projected Changes In Runoffmentioning
confidence: 99%
“…Irrigation demands are likely to be unmet in Mozambique and Zimbabwe, and hydropower generation is likely to be reduced in Zambia. 36,44 According to the simulations, air temperature and potential evaporation are projected to increase, while rainfall is projected to decrease, which together contribute to a decrease in river flows. Consequently, the decrease in water resources will lead to decreased hydropower production potential, by 9% in 2020s, 18% in 2050s and 28% in 2080s in the hydropower system, using A1B emission scenario.…”
Section: Projected Changes In Runoffmentioning
confidence: 99%
“…For instance, five GCMs were used in ZRB to analyse streamflow and found that part of the basin will experience decreasing percentage changes while some parts will have increasing percentage changes [16]. A large GCM ensemble data applied in the Zambezi River basin found that a series of potential impacts are more severe under RCP 8.5 than under RCP 2.6 or 4.5, indicating that Greenhouse Gas (GHG) mitigation may minimize uncertainties about the future climate scenarios, thereby reducing the risks of extreme changes as compared to the unconstrained emissions under RCP 8.5 [17]. GCM ensemble data were applied in Lake Victoria basin, Kenya and found that the range of change in mean annual rainfall of 2.4-23.2% corresponded to a change in streamflow of about 6-115% [18].…”
Section: Introductionmentioning
confidence: 99%
“…Results from these models serve as inputs into a water resources systems model, based on the approach of Sieber and Purkey (2007), for assessment of flood risk, hydropower output, and balancing of water supply and demand across competing uses. Fant et al (2015) describe the application of this modeling suite (CliRun, CliCrop, and water resources) to the countries in focus.…”
Section: Methodsmentioning
confidence: 99%
“…The baseline) mean runoff in billion cubic meters (BCM) and the percent difference between the mean and the 10th and 90th historical percentiles are shown below the basin name ([10th] mean [90th]). Source:Fant et al (2015)…”
mentioning
confidence: 99%